PWE-071 Etrolizumab induction in moderate/severe anti-TNF intolerant/refractory (IR) UC: the hickory open-label induction (OLI) trial. (8th June 2018) - Hayee, Bu'hussain; Rubin, David; Feagan, Brian; Oh, Young S; Arulmani, Udayasankar; Tyrrell, Helen; Maciuca, Romeo; Williams, Sarah; Tole, Swati; Thommes, James; Peyrin-Biroulet, Lauren
Abstract : Introduction: HICKORY OLI evaluated the safety and efficacy of etrolizumab (etro) via independent, centrally-read endoscopy, patient (pt)-reported outcomes, and inflammatory biomarkers in pts who are IR to aTNFs. Methods: Pts received etro 105 mg injected SC every 4 weeks (14 week induction). Mayo clinical subscores (MCS) based on endoscopic score (ES), and pt-reported rectal bleeding (RB) and stool frequency (SF) were assessed at baseline (BL) and week 14. Clinical response:≥3 point and 30% reduction of MCS from BL and ≥1 point decrease in RB or RB ≤1. Remission: MCS ≤2 with individual subscores≤1 and RB=0. Endoscopic improvement: ES ≤1. RB remission: RB=0; SF remission: SF ≤1 with≥1 point reduction from BL. The% decline from BL in RB and SF at week 14 was also calculated. Results: HICKORY OLI enrolled 130 UC pts; 45% had previously failed >1 TNF antagonist. BL disease activity included MCS score, 9.4; median C-reactive protein (CRP), 6.6 (95% CI: 2.9, 14.5) g/dL; and median faecal calprotectin (FC), 1778 (95% CI: 898, 3452) mg/kg. At week 14, etro treatment was associated with clinical response in 50.8% of pts; remission in 12.3%; ES ≤1 in 23.9%; RB remission in 52.3%; and SF remission in 35.4%. 43.9% of pts had ≥1 point improvement from BL in the ES score, and improved ES scores were associated with increased rates of RB and SF remission. Among pts with ES=0, 100% reported RB ≤1, and 90% reported SF ≤1 (table 1). Pts who achieved either SF or RB remission or ES ≤1 also demonstrated >50% geometric mean reduction in CRP (BL ≥2.87 mg/L) and >70% geometric mean reduction in FC. Conclusions: TNF antagonist-experienced pts with moderate-severe UC and high disease burden treated with open label etro for 14 weeks achieved clinically meaningful clinical response and remission and endoscopic improvement. Pts who had a decline in ES ≥1 achieved higher rates of RB and SF remission and greater reductions in inflammatory biomarkers. Recruitment to HICKORY continues in a randomised, placebo controlled induction cohort and a randomised maintenance phase is ongoing.